2008
DOI: 10.1103/physreva.78.013832
|View full text |Cite
|
Sign up to set email alerts
|

Two-color, nonlocal vector solitary waves with angular momentum in nematic liquid crystals

Abstract: The propagation and interaction of two solitary waves with angular momentum in bulk nematic liquid crystals, termed nematicons, have been studied in the nonlocal limit. These two spinning solitary waves are based on two different wavelengths of light and so are referred to as two-color nematicons. Under suitable boundary conditions, the two nematicons can form a bound state in which they spin about each other. This bound state is found to be stable to the emission of diffractive radiation as the nematicons evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 20 publications
0
51
0
Order By: Relevance
“…The variational approximate solutions will be based on a number of different, widely used trial functions in order to determine their absolute and relative accuracies. The details of these variational solutions have been given elsewhere [40,65], so they will only be summarized here. The three trial functions to be used are a hyperbolic secant [40], as this is the profile of the soliton solution of the (1 + 1)-D NLS equation, a Gaussian [35,37,65] and a hyperbolic secant squared, the last based on the exact solution (10).…”
Section: Variational Approximate Solutionsmentioning
confidence: 99%
“…The variational approximate solutions will be based on a number of different, widely used trial functions in order to determine their absolute and relative accuracies. The details of these variational solutions have been given elsewhere [40,65], so they will only be summarized here. The three trial functions to be used are a hyperbolic secant [40], as this is the profile of the soliton solution of the (1 + 1)-D NLS equation, a Gaussian [35,37,65] and a hyperbolic secant squared, the last based on the exact solution (10).…”
Section: Variational Approximate Solutionsmentioning
confidence: 99%
“…These modulation equations do not include loss to diffractive radiation [28,31] as it has been observed experimentally [25] and from theoretical solutions [29] that on the length scales of a typical cell this loss is very small and can be ignored. This point is taken up further in the …”
Section: Appendix: Shelf Radiusmentioning
confidence: 99%
“…An added complication with studying nematicons is that there is no known exact analytical solitary wave (nematicon) solution of the nematicon equations. Due to this, it has been found that a powerful approximate technique for studying this problem is that based on trial functions in variational formulations of the governing equations [26][27][28][29], this being an extension of modulation theory [30]. This technique is adapted and used in the present work.…”
Section: One Space Dimensionmentioning
confidence: 99%
“…3. Using the twocomponent equations re-written in a Lagrangian formulation [14], we employ the trial functions for the vortex, its soliton component and the director angle,…”
mentioning
confidence: 99%